Armenia’s Geopolitical Double-Cross Through the Lens of the Arms Trade - Teodor Detchev (Bulgarian Journal of International Economics and Politics, 2025)
The article examines the emerging cooperation in the field of armaments between the Republic of Armenia and France, focusing on the rapid development of military cooperation between the two countries and its specific dimensions. The varying political context of several deals with different types of arms are analysed. It is shown that in some transactions Armenia wins the favour of France, while in other cases there can be reasonable doubts that Armenia fulfils the orders of its ally – the Russian Federation. The analysis reveals unequivocally that Armenia’s intentions to purchase a large number of Caesar howitzers from France weakens the possibility of long-range artillery supplies to Ukraine and directly serves Russian interests in the war in Ukraine. The role of the Armenian state and private arms dealers in favour of Russia in the race with Ukraine to search for old Soviet and Russian weapons in 23 countries around the world is examined and analysed. These circumstances are analysed in the context of the fact that Armenia continues to be a military ally of Russia, and an Armenian military contingent is fighting on the Russian side at the front in Ukraine. It has been shown that the trend of limiting Armenia’s activity in the Collective Security Treaty Organization (CSTO) does not reduce the country’s closeness with Russia in the military field. The main lesson for the entire European Union from Armenia’s policy in the last two years should be the clear assumption that Armenia is playing a double game in which it has not at all abandoned its strategic ally – Russia.